Vascular Endothelial Growth Factor-A Levels in Term Neonates - Kandasamy, Yogavijayan; Hartley, Leo; Rudd, Donna (Journal of Child Science, 2017)
Vascular endothelial growth factor-A (VEGF-A) plays an integral role in physiological and pathophysiological angiogenesis and has increasingly been implicated in the development of retinopathy of prematurity (ROP) in preterm infants. Application of intravitreal anti-VEGF is frequently used to treat ROP with little consideration given to the role of VEGF-A in neonatal growth and development. Previous studies have demonstrated systemic anti-VEGF persistence, reduced peripheral VEGF levels following treatment, and possible diagnostic and prognostic uses for VEGF-A determination. This study seeks to determine a normal range for serum VEGF-A (sVEGF-A) in healthy, term infants. The sVEGF-A levels were obtained from 32 neonates born at term infants (16 males and 16 females) using an enzyme-linked immunosorbent assay. No significant correlations were found between sVEGF-A levels and time of sample collection, birth weight, or gender. The median sVEGF-A level was 976 (394–1635) pg/mL (95% confidence interval for median: 496–1,318 pg/mL). This preliminary study determines a normal range for the sVEGF-A level in healthy, term neonates. This normal range will provide a tool to assist in the diagnosis, prognosis, and monitoring of treatment of infants with ROP.
Keywords: vascular endothelial growth factor; term; neonates